The Effect of Leadership Style on Employee Motivation: A Case Study of Manufacturing Companies - Qin Xuefeng (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
This research set out to learn how different types of leadership in Chinese industrial businesses affect worker motivation. One hundred workers and ten supervisors from five Chinese manufacturing firms were surveyed and interviewed for this study. According to the results, both transformational and transactional leadership styles can boost employee motivation, but the latter is less successful at doing so than the former. Job satisfaction, work-life balance, recognition and rewards, job security, and professional advancement opportunities were also variables that influenced employee motivation. Managers in China's manufacturing sector can put these findings to use by prioritizing the adoption of transformational leadership styles and addressing variables that influence employee motivation, as indicated by the study's findings. More study into the connection between leadership style and employee motivation in China's manufacturing sector could benefit from a larger sample size and a mixed-methods approach.